LANGUAGE ATTITUDE OF THE PEOPLE AROUND THE BORDER OF EAST NUSA TENGGARA AND TIMOR LESTE: A LANGUAGE ATTITUDE STUDY IN SILAWAN VILLAGE, THE PROVINCE OF EAST NUSA TENGGARA - Sri Winarti (Metalingua: Jurnal Penelitian Bahasa, 2015)
THIS writing discusses people's language attitude in the border area of East NusaTenggara -Timor Leste, particularly in Silawan village, East Tasifeto district,Belu regency, the Province of East Nusa Tenggara. This study aims to describethe people's language attitude in the border area on the Indonesian language,local language, and foreign language using a survey method. The samples aretaken from the population and the data are collected via questionnaires. It is aquantitative study correlating respondent social features with their opinion tosome language attitude parameters, namely their language attitude on theIndonesian language, local language, and foreign language. It is found thatpeople living around the border area of East Nusa Tenggara have more positiveattitude towards the local language than towards the Indonesian language, orthe foreign language. The social features of speakers, such as gender, ages,education levels, spouse ethnicities, marital statuses, and residences influenceone's language attitude. The language attitude of people living around the borderarea, either on the Indonesian language, on local language, or on foreignlanguage, based on their social features displays various results